Numerical analysis of low-velocity impact of carbon-basalt/epoxy hybrid laminates - Maper, A. (National Institute of Science Communication and Information Resources (NISCAIR), 2019)
In this paper, an attempt has been made to numerically investigate the transient dynamic response of carbon-basalt/epoxy laminated composites subjected to low velocity impact. Carbon laminates are expensive hence, inclusion of cheaper basalt to obtain an improved, yet economical laminate is necessary. Finite element analysis (FEA) technique has been employed to simulate the laminated models. Loading profiles and test conditions from drop-weight tests have been obtained from literatures and necessary validation of FEA has also been performed. A correlation between impactor mass and velocity on the maximum laminate centre deflection has been established. In addition, the influence of hybrid stacking sequence and carbon position in the hybrid on laminate damage response has been studied. It has been observed from the study that hybrid 3 (H3) with stacking sequence CCBC-2 (best combination) showed the least deflection of all the stacking sequence sets and has the lowest deflection in all the low velocity impact testing conditions. Â© 2019, National Institute of Science Communication and Information Resources (NISCAIR). All rights reserved.